Insights Into the Species-Specific Microbiota of Greenideinae (Hemiptera: Aphididae) With Evidence of Phylosymbiosis - Qin, Man; Chen, Jing; Jiang, Liyun; Qiao, Gexia (Frontiers in Microbiology, 2022)
Aphids and their symbionts represent an outstanding model for studies of insect-symbiont interactions. The aphid microbiota can be shaped by aphid species, geography and host plants. However, the relative importance of phylogenetic and ecological factors in shaping microbial community structures is not well understood. Using Illumina sequencing of the V3−V4 hypervariable region of the 16S rRNA gene, we characterized the microbial compositions of 215 aphid colonies representing 53 species of the aphid subfamily Greenideinae from different regions and plants in China, Nepal and Vietnam. The primary endosymbiont Buchnera aphidicola and secondary symbiont Serratia symbiotica dominated the microbiota of Greenideinae. We simultaneously explored the relative contribution of host identity (i.e., aphid genus and aphid species), geography and host plant to the structures of bacterial, symbiont and secondary symbiont communities. Ordination analyses and statistical tests highlighted the strongest impact of aphid species on the microbial flora in Greenideinae. Furthermore, we found a phylosymbiosis pattern in natural Greenideinae populations, in which the aphid phylogeny was positively correlated with microbial community dissimilarities. These findings will advance our knowledge of host-associated microbiota assembly across both host phylogenetic and ecological contexts.